No evidence of queen immunisation despite transgenerational immunisation in Crematogaster scutellaris ants. (January 2020) - Bordoni, Adele; Tatini, Irene; Puente Romero, Cristina; Perito, Brunella; Turillazzi, Stefano; Dapporto, Leonardo
Graphical abstract: Highlights: C. scutellaris queens are less resistant to M. anisopliae after a first exposure. Workers are known to be more resistant if queens experienced this pathogen. Immunisation and trans-genarational immunisation are uncoupled phenomena. Abstract: Like vertebrates, invertebrates evolved acquired immunity based on memory-like mechanisms, known as immunisation. Immunisation and its transmission among individuals are phylogenetically ancestral and conserved characters that have been reported in different insect orders. Physiological mechanisms are still largely unknown, and the high variability in responses in different host-parasite systems led to different conclusions. In social insect species, the complex organisation of colonies further complicates the interpretation of the immune responses. In ants, it has been shown that the expression of immunisation depends on species, caste and physiological status of individuals. In this study, we investigate the occurrence of immunisation in queens of Crematogaster scutellaris ants using the fungus Metarhizium anisopliae as elicitor. Foundation in C. scutellaris is claustral and monogynic, allowing us to test the existence of the phenomenon in two distinct physiological conditions, corresponding to the claustral and colonial phases of queens. Queens and foundresses challenged with heavy doses of the pathogen showed higher mortality if previously exposed to light doses, indicating the absence of immunisation in our experimental settings. On the other hand, evidence of the trans-generational immunisation in the same host-parasite system has been recently found, where workers produced by queens exposed to light doses of M. anisopliae survived longer than those belonging to the control group. These results indicate that foundresses exposed to M. anisopliae can elicit an increased resistance in the offspring without providing themselves with a similar increased immune response and that immunisation and trans-generational immunisation are uncoupled phenomena in this host-parasite system.